Development of Iron and Zinc Enriched Meat of Japanese Quails as Functional Food - Sannamani, Prakash; Jayanaik; Pal, D.T.; Reddy, K. Venkata; Renukaprasad , C. (Journal of Meat Science, 2012)
A study was carried out to develop iron and zinc enriched meat as functional food by supplementing organic Fe and Zn to Japanese quails. A total of 600 day old quail chicks were allotted to five treatment groups (T1 to T5) of 120 chicks each with four replicates consisting of 30 birds per replicate. Control diet (T1) was formulated by incorporating inorganic iron (120 mg/kg) and zinc (25 mg/kg) according to NRC (1994) specifications. For each of the treatments (T2-T5), inorganic Fe and Zn of control diet were replaced by organic Fe (Fe-methionine) and Zn (Zn-methionine) at recommended level (T2), two (T3), three (T4) and four times (T5) of NRC (1994) recommendations. The results at the end of 6th week showed that carcass characteristics, organ weights and sensory evaluation did not significantly different among dietary treatments. The Fe content was significantly (Pd”0.01) higher in T3 (240 mg/kg Fe-methionine) for breast, thigh, liver and heart and in T4 (360 mg/kg Fe) group for gizzard and minced meat when compared to control group having inorganic Fe (120 mg/kg). The Zn content was significantly higher in T5 for breast and in T4 for thigh, liver and heart. In minced meat the Fe and Zn content was significantly (P
Keywords: Quail; organic iron; zinc; carcass characteristics; muscle; heart; liver; gizzard; tibia